Implement the Harmonic Search Algorithm with Optimum Location of Capacitors Sizing and Dispatchable DGs to Control the Reactive Power on Interconnected Bus System - M. Suneetha; R.Srinivasa Rao; B. Subramanyam (Institute of Advanced Engineering and Science, 2018)
Power system is combination of generation, transmission and Distribution Network. In modern trends power system operation is very difficulty due to energy storage elements, and variable inductive load. In power system, control the reactive power is essential to maintain the safe and more reliability of power system operation. In this paper, to organize the real power and reactive power by optimizing and sizing of capacitors and Dispatchable Distribution generators in a distribution network with help of Harmonic Search Algorithm. The constraints of power system like voltage, real power and reactive and branch current carrying capacity are included in the evaluation of the objective function. To validate planned development network an IEEE 30 bus investigation system is considered.